PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN - Sri Hastuti (Ekonomika, 2020)
Data retrieval method used in this study is literature study is a method used toobtain theoretical data related to the issues discussed. Then field studies are interviews,observations, related to the problem under study to obtain clear data. Based on theresults of research that has been done on Laundry Ananda Lahat, and the results of theanalysis of the Influence of Service Quality and Price Against Consumer Satisfaction canbe drawn conclusion as follows: In t test obtained there is a significant influence of thevariable Quality Service (X1) on Consumer Satisfaction while the variable Price (X2) hasno effect on Consumer Satisfaction (Case Study On Laundry Ananda Lahat). In F testobtained there is a linear relationship between Quality of Service (X1) and Price (X2)simultaneously or simultaneously have a significant influence on Consumer Satisfaction(Case Study On Laundry Ananda Lahat) (Y). Of the two factors namely Quality of Serviceand Price which has the most dominant influence on Consumer Satisfaction (Case StudyOn Laundry Ananda Lahat) is Quality Service.